Empowerment of Elementary School Students to Improve Knowledge and Behavior on Physical Activity through Practice-Based Education - Syahrir, Sukfitrianty; Adha, A. Syamsiah (Unihealth Community Research, 2025)
This empowerment program aimed to develop trained peer counselors by providing knowledge and skills on physical activity. The program was conducted at SD Negeri Samata involving 25 fifth-grade students. It consisted of a one-day training and practical sessions including exercise routines. The pre-test results showed that most students had low levels of knowledge, while the post-test indicated a significant improvement in both knowledge and behavior. All students effectively served as peer educators. This program has the potential to be integrated as a routine extracurricular activity to promote physical health awareness in schools.